The present-day kinematics of the Tianshan orogenic belt constrained by GPS velocities - Chong Gu; Bin Zhao; Tianchen Sheng; Wei Wang; Dongzhen Wang; Daiqin Liu; Jie Li; Pinji Lv; Xuejun Qiao (Geodesy and Geodynamics)
Since the late Cenozoic, the reactivated Tianshan orogenic belt has accommodated crustal shortening exceeding 200 km, primarily due to the far-field effects of the India-Eurasia plate collision. However, the details of the strain partitioning in the Tianshan Mountain range remain elusive. We interpret a new compilation of GPS velocities covering the whole Tianshan range with a classic elastic block model. Compared to previous studies with a block modeling approach, the Tianshan orogenic belt is further subdivided into several blocks based on geological fault traces and a clustering analysis approach. In addition to obvious crustal shortening on the bounding thrust faults of the Tianshan, our inverted fault slip rates also reveal that faults within the Tianshan orogenic belt, such as the Nalati Fault and the southern margin of the Issyk-Kul Lake Fault, which plays a crucial role in accommodating the tectonic crustal shortening. In the 72°E−78°E region, the internal shortening rate within the mountain is approximately 5–7 mm/yr. Besides crustal shortening, strike-slip motion occurs on faults in the interior of the mountain range as well as in the foreland fold-and-thrust belts, especially in the southern margin of the Tianshan. These findings suggest that the crustal deformation in the Tianshan Mountain range is more complex than previously thought, and the oblique convergence between the Tarim Basin and the Tianshan probably results in both strike-slip and thrust motion.